EVALUATION OF THE EFFECTIVENESSOF PHYSIOTHERAPYBASED ON THE LOCATIONTHE JOINTCHANGESIN RHEUMATOID ARTHRITIS - Agnieszka Krawczyk-Wasielewska; Ewa Mojs; Roksana Malak; Przemysław Keczmer; Piotr Kalmus; Dariusz Łucka; Włodzimierz Samborski (European Scientific Journal, ESJ, 2014)
Rheumatoid arthritis (RA) is a chronic connective tissue disease. Typical first signs of diseases are pain and edemas of small hand and foot joint, but sometimes first symptoms regard less typical place like one big joint. Pain became the barrier for normal functioning patients with RA, therefore wide range of physical therapy is needed. The aim of this study was evaluation of pain reduction in physical therapy on diseases changed joint. The study involved 50 patients with RA, where mean of age was 47,5. In this group fallowing physical therapy techniques were used: cryotherapy, ultrasound therapy, laser therapy, electrical stimulation TENS, iontophoresis, diadynamic and magnetic therapy. In studied group first signs of diseases were similar like in literature. The presented results indicate pain reduction on all treatment filled join. Used physical therapy techniques were more effective on hand joints then on foot joints.